Reparation for violations of human rights and humanitarian law: the responsibility of international organizations - Ferstman, C (2015)
This thesis is concerned with reparation for human rights and international humanitarian law breaches committed by or attributed to international organizations. These breaches constitute internationally wrongful acts which according to the International Law Commission’s Draft articles on the responsibility of international organizations, give rise to an obligation on the offending organization to afford reparation. However, in practice, the obligation to afford reparation is unimplemented. The thesis explores why this is. The thesis considers how the law of responsibility intersects with the specialised regimes of human rights and international humanitarian law and particularly, their application to remedies and reparation owed to individuals. It reviews the various gaps in the normative framework and the limitations of existing redress mechanisms. The thesis analyses the cogency of the arguments and rationales that have been used by international organisations to limit institutional liability and the scope and functioning of redress mechanisms, included by the resort to lex specialis principles. It is postulated that the standards of reparation must be drawn from the nature of the breach and the resulting harms and not by who is responsible for the breach. In this respect the thesis is an exercise in the progressive development of the law. Having determined that existing redress mechanisms cannot afford adequate or effective remedies and reparation, the thesis explores how to move towards a model that achieves greater compliance. Indeed, should it be accepted that international organizations must afford remedies and reparation for breaches of human rights and IHL that correspond to the standards that exist in those specialised fields then it is argued that there is a corresponding obligation on them to put in place the modalities for that to be achieved.